(untitled) - Charles W. L Hill (Boston, 1997)
The book explains how and why the world's countries differ; presents a thorough review of the economics and politics of international trade and investment; explains the functions and form of the global monetary system; examines the strategies and structures of international business; assesses the special roles of an international business's various functions
Keywords: competition, international,international business enterprises - management